Effect of Using Nanoparticle-based Diesel Fuel on Enhancement of Performance and Emissions of Diesel Engines - Gadalla, Mamdouh A.; Mazen, Omar M.; Aboul-Fotouh, Tarek M.; Ashour, Fatma H.; Elazab, Hany A. (Nanoscience & Nanotechnology-Asia, 2021)
Background: The current research work reports an investigation of the effects of employing CuO and TiO2 nanoparticles as potential additives to refinery (petroleum) diesel fuel, in order to reduce the emissions of combustion process as well as to enhance the combustion process. Methods: Nanodiesel samples were prepared with various concentrations (50 ppm, 100 ppm, 200 ppm, 300 ppm). The experimental work was conducted using a four stroke diesel engine with a single cylinder at various loads in order to accurately determine the influence of nanoparticles on combustion process. The experimental readings were measured at two conditions, cold start and hot start relative to the engine. Results: It was clearly observed that the nanodiesel fuels have significantly reduced CO, CO2, NO, unburned HC, and enhanced the engine performance. According to the experimental results the 100 ppm TiO2 and 200 ppm CuO nanodiesel have showed almost the highest performance and lowest emissions comparable to neat diesel fuel and other nanodiesel samples. Owing to 100 ppm TiO2 on hot start conditions, it was found that the CO, CO2, NO, unburnt HC, exhaust temperature, and BSFC have been reduced by 41.4%, 37 %, 38.3%, 81%, 4.9%, and 20.5% respectively at maximum load. Meanwhile, the brake power, RPM and thermal efficiency have increased by 1.5%, 1% and 2.65% respectively. Conclusion: Eventually the stability of nanodiesel fuels were investigated. Accordingly, the stability of 100 ppm TiO2 and for 200 ppm CuO are 7 days and 3 days.
Keywords: exhaust